Orbital Simulations for Directed Energy Deflection of Near-Earth Asteroids. (2015) - Zhang, Qicheng; Walsh, Kevin J.; Melis, Carl; Hughes, Gary B.; Lubin, Philip
Abstract: Directed energy laser ablation at the surface of an asteroid or comet produces an ejection plume that will impart a thrust on the asteroid. This thrust can mitigate a threatened collision with the Earth. This technique uses the asteroid itself as the deflection propellant. The DE-STAR laser system is designed to produce a sufficiently intense spot on the surface of an asteroid to accomplish this in one of two operational modes. One is a complete "stand-off" mode where a large space based phased-array laser directed energy system can interdict asteroids at large distances allowing sufficient time to mitigate nearly all known threats. A much smaller version of the same system, called DE-STARLITE, can be used in a "stand-on" mode by taking a much smaller laser to the asteroid and slowly deflecting it over a sufficiently long period of time. Here we present orbital simulations for a range of near-Earth asteroid impact scenarios for both the stand-off and stand-on systems. Simulated orbital parameters include asteroid radius and composition, initial engagement time, total laser-on time and total energy delivered to target. The orbital simulations indicate that, for exposures that are less than an orbital time, the thrust required to divert an asteroid is generally inversely proportional to laser-on time, proportional to target mass and proportional to the desired miss distance. We present a detailed stand-on scenario, consistent with current dedicated mission capabilities, to show the potential for laser ablation to allow significant deflection of targets with small systems. As one example we analyze a DE-STARLITE mission scenario that is in the same mass and launch envelope as the proposed Asteroid Redirect Mission (ARM) but using a multi kilowatt class laser array capable of deflecting a 325 m diameter asteroid with 2N of thrust for 15 years in a small fraction of even the smallest SLS block 1 launch vehicle configuration.